2005
DOI: 10.1159/000088854
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Nitric Oxide-Sparing Actions of Dihydropyridines and ACE Inhibitors Differ in Human Endothelial Cells

Abstract: The effects of dihydropyridine Ca2+ channel blockers (DHP) and ACE inhibitors on superoxide formation and nitric oxide (NO) bioavailability were compared in human EA.Hy926 endothelial cells (EC). EC were stimulated 4 h with angiotensin II (Ang II, 10 nM) ± study drugs. Specific superoxide formation was measured by lucigenin-enhanced chemiluminescence, reduction of cytochrome c and rhodamine-123 fluorescence. Free NO release was determined with an amperometric NO sensor. NADPH oxidase subunits expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…This improvement may result from vasodilatory action in insulin-sensitive tissues without SNS stimulation [118], prevention of the inhibition of glucose transporters and glycogen synthase by calcium [7], or various antioxidant effects [7,119]. Antioxidant effects include inhibition of Ang II-and aldosteroneinduced superoxide formation [120,121], improvement in NO bioavailability [120,121], and reduction of oxidative stress [122,123]. CCBs have minimal effects on lipid levels [117,118,124,125].…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This improvement may result from vasodilatory action in insulin-sensitive tissues without SNS stimulation [118], prevention of the inhibition of glucose transporters and glycogen synthase by calcium [7], or various antioxidant effects [7,119]. Antioxidant effects include inhibition of Ang II-and aldosteroneinduced superoxide formation [120,121], improvement in NO bioavailability [120,121], and reduction of oxidative stress [122,123]. CCBs have minimal effects on lipid levels [117,118,124,125].…”
Section: Mechanismsmentioning
confidence: 99%
“…They may improve lipid levels by improving carbohydrate metabolism [125]. Their antioxidant effects include suppression of Ang II-induced superoxide formation [120,121] and reduction in oxidative stress [148,149]. ACE inhibitors have several pancreatic benefits.…”
Section: Mechanismsmentioning
confidence: 99%
“…Thus the potential role of calcium-dependent reactive oxygen species (ROS) production in human coronary artery disease remains unknown. Interestingly, it has been reported that calcium channel antagonists reduce ROS production in human endothelial cells (8). These drugs have been demonstrated to be clinically beneficial in improving clinical outcomes in patients with vascular diseases, particularly coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…Amlodipine facilitates NO release, possibly via upregulation of the endothelial isoform of NOS (i.e., eNOS). The findings from several preclinical studies [25][26][27][28][29] are consistent with such a mechanism.…”
Section: Amlodipinementioning
confidence: 53%
“…Second, ACE inhibition may reduce angiotensin II-associated production of smooth muscle cell oxygen radicals that inactivate endothelial nitric oxide [45]. In human endothelial cells, the ACE inhibitors captopril and ramiprilat (but not enalaprilat) reduced angiotensin II-stimulated intracellular ROS [28]. In a separate study [29], also conducted in human endothelial cells, both captopril and enalaprilat again inhibited intracellular superoxide formation; however, captopril additionally inhibited superoxide formation extracellularly.…”
Section: Renin-angiotensin-aldosterone System Inhibitorsmentioning
confidence: 99%